Pengaruh Substitusi Ion Mn dan Ion Co Serta Ion Ti pada Pembentukan Fasa dan Sifat Magnetik Barium Hexaferrite BaFe9(MnCo)1,5Ti1,5O19 Disintesis Melalui Rute Metallurgi Serbuk - Priyono P; Eddy Siradj; Azwar Manaf (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2013)
Barium ferrite with hexagonal molecular BaFe12O19 is well-known for its high performance permanent magnetic and good mechanical properties and attracted attention of researchers for a long time. The hexaferrite powders were produced according to a conventional ceramic process with powder metallurgy method. Moreover, the powders were analyzed by X-ray diffraction, to detect the presence of secondary phases. The magnetic properties of the sampleswere measured at room temperature using Permeagraph with a maximum applied field of 1.5 T. The calculation of the lattice parameter on conventional magnets (BaFe12O19) results a = b = 5,894 Å and c = 23,210 Å, while the substituted phase has a range value of a = b between 5,893 Å to 5,899 Å, and c lattice parameter value is in the range of 23,328 ˚A to 23,346 Å.With the partial substitution of Fe+3 ions by Mn+2 ions, ion Co+2 and Ti+4 ion magnetic properties decrease primarily on the magnetic coercivity from 125 kA / m (conventional) to ~ 5 kA /m in the substituted materials.